Management of resistant distal femur non-unions with allograft strut and autografts combined with osteosynthesis in a series of 22 patients - Kanakeshwar, RB; Jayaramaraju, D; Agraharam, D; Rajasekaran, S (Elsevier, 2017)
Introduction and Purpose: Challenges to the surgeon in managing cases of resistant non-union of the distal femur include poor bone stock, disuse osteopenia and joint contractures. Procedures varying from simple bone grafting to megaprosthesis revision have been described. We successfully managed such cases using our technique of combining cortical allograft struts to augment the defect in the femoral condyle coupled with autogenous iliac crest bone grafting and locking plate osteosynthesis.